Policy, regulation, and innovation in China's electricity and telecom industries - Brandt, Loren; Rawski, Thomas G., 1943- (Cambridge : Cambridge University Press, 2019)
The scale of China's innovation ambitions inspires worldwide commentary, much of it poorly informed. Focusing on electricity, telecommunication and semiconductors, this book offers a richly detailed account of China's innovation efforts. Massive application of human, policy and financial resources shows great promise, but institutional obstacles, conflicting objectives, ill-advised policies and Soviet-era legacies inject inefficiencies, resulting in a complex mosaic of success and failure in both technical and commercial dimensions. State Grid leads the world in high-voltage power transmission, while domestic semiconductors lag behind the international frontier. Electricity and telecom providers record impressive technical advances, but overinvestment and inefficient operation contribute to high costs and prices. Nuclear power combines technical excellence with commercial weakness. Cost reduction rather than new technology underpins commercial success in solar materials. The book's granular studies look beyond specific technologies to incorporate the policy matrix, regulatory structures and global developments into the appraisal of China's innovation achievements.
Title from publisher's bibliographic system (viewed on 30 May 2019).
Keywords: Electric utilities -- China; Telecommunication -- China